Getting Started in Interpreting Research : Methodological reflections, personal accounts and advice for beginners. - Gile, Daniel; Dam, Helle V.; Dubslaff, Friedel; Martinsen, Bodil; Schjoldager, Anne. (Philadelphia : John Benjamins Publishing Company, 2001)
What sets this collection apart in the literature is its direct, personal style. Experienced supervisors as well as younger scholars speak to beginning researchers in interpreting, and more generally in Translation Studies. The contributors, who are very familiar with the difficulties beginners experience, focus on their needs and anticipate their questions. They reflect, analyze and advise, with illustrations from their own experience.Issues discussed include topic selection, project planning, time management, 'doctoral stress', the use of the literature, critical reading and book reviews, supervisor-supervisee relations, institutional frameworks for research training, issues in empirical research, theoretical analysis, and the role of small projects. Readers will thus find answers to many personal, institutional and methodological questions, which are common to beginners in many disciplines and in many paradigms.
Getting Started in Interpreting Research -- Editorial page -- Title page -- LCC data -- Table of contents -- Introduction -- Selecting a topic for PhD research in interpreting -- Critical reading in (interpretation) research -- Reporting on scientic texts -- Writing a dissertation in translation and interpreting -- MA theses in Prague -- Interpretation research at the SSLMIT of Trieste -- Small projects in interpretation research -- Doctoral work on interpretation -- Beginners' problems in interpreting research -- The manipulation of data -- Approaching interpreting through discourse analysis -- Working within a theoretical framework -- Reflective summary of a dissertation on simultaneous interpreting -- Conclusion -- About the contributors -- Abbreviations and acronyms -- Name index -- Concept index -- The BENJAMINS TRANSLATION LIBRARY.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Translating and interpreting -- Research; Electronic books